Assessing the scale and readiness of companies to enter the world market of informational technologies - Sokol, Kateryna (2013 L'Association 1901 "SEPIKE", 2015)
In the article while determining the readiness assessment of IT companies to enter the world market of information technology, which is based on the weighted average degree of manifestation of expert evaluation in its totality of diagnostic parameters that characterize readiness to enter the world market of information technologies and can manifest itself in its activities to varying degrees, is proposed to use specially designed numerical measurement scale that has a gradation in the proportions of the golden section, corresponding to different degrees of readiness of the IT companies to enter the world market of information technologies.
Keywords: scale evaluation; Delphi method; IT company; average expert assessment; principle of the golden section; Fibonacci numbers